Tussen sciëntisme en fideïsme: Acceptatie van de evolutietheorie als theologische uitdaging - Brink, Gijsbert van den (HTS teologiese studies, 2014)
Between scientism and fideism: Acceptance of evolution as a theological challenge. In this contribution to the special issue of HTS Teologiese Studies/Theological Studies that is dedicated to Prof. Buitendag, I will explore what Prof. Buitendag’s notion of a ‘revised natural theology’ might mean for the theological reception of the scientific theory of biological evolution. I argue that two extremes must be avoided here. One is the fideistic ignoring of (or refusal to take into account) the data that have been placed on the table regarding the evolutionary development of life on earth, as if these do not concern theology. The other extreme that theology must steer clear of is a scientistic over-interpretation of our knowledge of the evolutionary past, whereby the theory of evolution is magnified to a comprehensive philosophy of life (‘evolutionism’) that is incompatible with Christian faith.